2020
DOI: 10.1111/cea.13551
|View full text |Cite
|
Sign up to set email alerts
|

Maternal psychological distress before birth influences gut immunity in mid‐infancy

Abstract: Background: Maternal pre-postnatal psychosocial distress increases the risk for childhood allergic disease. This may occur through a host immunity pathway that involves intestinal secretory immunoglobulin A (sIgA). Experimental animal models show changes in the gut microbiome and immunity of offspring when exposed to direct or prenatal maternal stress, but little is known in humans. Objective:We determined the association between maternal depression and stress symptom trajectories and infant fecal sIgA concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
(56 reference statements)
0
24
0
Order By: Relevance
“…Nine studies on the association between antepartum depression and exclusive breastfeeding at 3 to 6 months postpartum were identified. Most of these studies measured antepartum depression during either the second or third trimester (Abdul Raheem et al, 2019; Ahlqvist-Björkroth et al, 2016; Coo et al, 2020; Figueiredo et al, 2014; Kang et al, 2020; Rahman et al, 2016), with one assessing this during the first trimester (Do et al, 2021). Two studies assessed antepartum depression during more than two trimesters (Figueiredo et al, 2014; Verbeek et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies on the association between antepartum depression and exclusive breastfeeding at 3 to 6 months postpartum were identified. Most of these studies measured antepartum depression during either the second or third trimester (Abdul Raheem et al, 2019; Ahlqvist-Björkroth et al, 2016; Coo et al, 2020; Figueiredo et al, 2014; Kang et al, 2020; Rahman et al, 2016), with one assessing this during the first trimester (Do et al, 2021). Two studies assessed antepartum depression during more than two trimesters (Figueiredo et al, 2014; Verbeek et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, restraint stress in a murine model raised the extent of gut IgA binding of microbiota like the Lachnospiraceae; this result was replicated in fecal samples from adults with irritable bowel syndrome, a condition often aggravated by stress (Rengarajan et al, 2020). Kang et al (2020) published the first human report regarding the independent association between maternal depressive symptomatology during pregnancy and compromised gut immunity in offspring. This recent study which examined infant fecal sIgA concentrations in relation to maternal depression trajectories, revealed that infants born to mothers in the prenatal trajectory (high depressive symptoms scores primarily during pregnancy) were twice more likely to have lower sIgA concentrations than infants of mothers with low symptom scores.…”
Section: Prenatal Depression Affects Infant Gut Immunity Independent Of Breastfeedingmentioning
confidence: 91%
“…There are examples in the literature of maternal depression being associated with offspring immune functioning. For example, in a large cohort study, antenatal depression, but not postnatal depression, was associated with reduced infant faecal secretory immunoglobulin A (sIgA) concentrations, independently of breastfeeding status ( Kang et al., 2020 ). These alterations as a result of maternal affect may be especially salient in certain subgroups, for example in a study which compared preterm with term births, it was found that in the preterm group only, maternal negative emotions (defined as depressive symptoms or negative affect) were positively associated with levels of IL-6, -8, -10, −13 and −18 in the cord blood, as well as maternal levels of IL-6 and -8 ( Fransson et al., 2012 ).…”
Section: Offspring Outcomesmentioning
confidence: 99%